Influence of Sea Level Rise on Storm Surges in the Pearl River Estuary - HU Yaohui; WANG Zhili; ZHANG Juan; WU Yufu (Renmin Zhujiang)
The sea level rise ensuing from climate change has gravely imperilled the safety of coastal engineering in coastal regions. A coupled model of astronomical tide and storm surge was constructed to perform a numerical simulation of the storm surge in the nearshore sea area of the Pearl River Estuary. The model was validated by utilizing the observational data under historical typhoon events. The research outcomes reveal that: ① The influence exerted by a sea level rise of 1 m on the astronomical tide level is more conspicuous than that by a sea level rise of 0.45 m. Concurrently, sea level rise augments the astronomical tidal range. ② The impact of sea level rise on the water level increase of storm surge is not substantial. Simultaneously, the variation of water level increase of storm surge within the Pearl River Estuary exhibits a spatially non-uniform characteristic, with an escalation in water level on the northeastern side and a reduction on the southwestern side of the Pearl River Estuary. ③ The ascent of sea level will give rise to an earlier peak water level of the storm surge. For instance, in the case of a sea level rise of 1 m, the peak water level at Chiwan Station is advanced by 10–15 minutes. Sea level rise not only exerts an influence on the astronomical tide levels but also has an impact on the occurrence time of the peak water level of storm surges, thereby presenting novel challenges to flood control measures in coastal regions. Moreover, the influence of sea level rise varies among different areas, and distinctive coping strategies need to be implemented for specific regions.